2021
DOI: 10.2147/amep.s290142
|View full text |Cite
|
Sign up to set email alerts
|

The Satisfaction Level of Undergraduate Medical and Nursing Students Regarding Distant Preclinical and Clinical Teaching Amidst COVID-19 Across India

Abstract: Background The COVID-19 pandemic has disrupted the educational system and led to a drastic shift of professional undergraduate teaching for medical and nursing students into online mode. Methods This was a cross-sectional, observational questionnaire-based study to assess the satisfaction level of the students. The questionnaire had 25 items of which 23 were questions with responses on the Likert scale and two items on views and suggestions were open-ended. The online q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
70
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(84 citation statements)
references
References 17 publications
9
70
0
5
Order By: Relevance
“…In Nepal, some students (31.6%) denoted electricity cut down as the factor behind internet disturbance, 47.4% and 19.6% found satisfactory and good internet connection respectively [16] . An Indian study on 1068 students observed poor internet accessibility with audio visual problem, costly internet package ascribed to increased cost for online class as barriers [24] and this observation actually supports this study. Another study conducted in Sri Lanka also pointed lack of reliable network infrastructure as one of the major constraint for WBL [25] .…”
Section: Discussionsupporting
confidence: 83%
“…In Nepal, some students (31.6%) denoted electricity cut down as the factor behind internet disturbance, 47.4% and 19.6% found satisfactory and good internet connection respectively [16] . An Indian study on 1068 students observed poor internet accessibility with audio visual problem, costly internet package ascribed to increased cost for online class as barriers [24] and this observation actually supports this study. Another study conducted in Sri Lanka also pointed lack of reliable network infrastructure as one of the major constraint for WBL [25] .…”
Section: Discussionsupporting
confidence: 83%
“…Due to the COVID‐19 outbreak, all universities postponed the start of the spring semester. Therefore, the traditional campus‐based nursing educational mode was changed, and online teaching has since become the primary teaching method (Dutta et al., 2021). In addition, interns left the hospitals, and clinical practice was suspended (Rose, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…
our article titled "The Satisfaction Level of Undergraduate Medical and Nursing Students Regarding Distant Preclinical and Clinical Teaching Amidst COVID-19 Across India". 1 Concerning to the first query, we deeply agree with the fact that "satisfaction" is a broad concept and has varied domains. With regard to describing a particular type of teaching style, we would like to notify that the present study analyzed the online teaching of the medical and nursing students owing to the abrupt change in the pattern of teaching from physical lectures and practical exercises to complete online mode due to lockdown and isolation recommendations from the administration and government.
…”
mentioning
confidence: 52%